2014
DOI: 10.1371/journal.pone.0092289
|View full text |Cite|
|
Sign up to set email alerts
|

Microsporidia Detection and Genotyping Study of Human Pathogenic E. bieneusi in Animals from Spain

Abstract: Microsporidia are ubiquitous parasites infecting all animal phyla and we present evidence that supports their zoonotic potential. Fecal samples taken from domestic (cats and dogs), farm (pigs, rabbits and ostriches) and wild animals (foxes) from different provinces of Spain were evaluated for microsporidia infection by light microscopy and PCR. After Microsporidia species identification, E. bieneusi genotypes were additionally studied by sequence analysis of the ITS region. Eighty-five samples out of 159 exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 43 publications
8
78
2
Order By: Relevance
“…The prevalence of E. bieneusi found in this study (59.3%) was higher than those reported in other studies worldwide [18,24,26,40,56,63,66,67,[71][72][73][74], with exception of two studies, one in the Czech Republic, where 94% of 79 pigs were found E. bienesi-positive [37] and one in China, where 83.2% and 89.5% of the 95 pigs studied were positive for E. bienesi using SSU rRNA or ITS genes, respectively [65].…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of E. bieneusi found in this study (59.3%) was higher than those reported in other studies worldwide [18,24,26,40,56,63,66,67,[71][72][73][74], with exception of two studies, one in the Czech Republic, where 94% of 79 pigs were found E. bienesi-positive [37] and one in China, where 83.2% and 89.5% of the 95 pigs studied were positive for E. bienesi using SSU rRNA or ITS genes, respectively [65].…”
Section: Discussioncontrasting
confidence: 79%
“…Here, E. bieneusi was only found in 14.7% (22/150) of Rex rabbits, and the prevalence was higher than that (0.94%; 4/426) reported in a recent study in China [57]. To our best knowledge, there are another two studies reporting E. bieneusi infections in rabbits, where only a small number of rabbits were involved [11, 13]. The present finding of C ryptosporidium and E. bieneusi in the asymptomatic rabbits emphasized the importance of epidemiological investigations of the two pathogens in these animals.…”
Section: Discussionmentioning
confidence: 65%
“…Compared to genotypes D and Type IV, genotypes Peru6 and I have a small number and a limited geographical area in human cases infected with E. bieneusi , with the former only found in Peru and Portugal [4, 8, 31, 49], and the latter only in China [56]. In China, to date, genotype Peru6 has been identified in sheep and goats, reindeers, red-crowned cranes, ducks, geese, and pigeons, as well as in wastewater [25, 29, 62, 63]; genotype I has been found in nonhuman primates, cats, a chicken, pigeons, pigs, and golden takins [13, 16, 17, 37, 39, 59, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…These genotypes were previously considered to be highly specific to cattle and genetically segregated from the genotypes found in humans and pigs (20). However, as shown in Table 2, like BEB6, genotypes BEB4, I, and J also have expanded host ranges, with BEB4 also infecting humans from the Czech Republic and pigs from China (11,44), I infecting monkeys from China, deer from the United States, pigs from Spain, and cats from China (35,41,42,45), and J infecting deer from the United States, chickens from Germany, and birds from Iran (35,46,47). A recent survey from Qinghai Province, northwest China, characterized E. bieneusi group 1 genotypes CHN11 (4/23 specimens) and CHN12 (1/23 specimens) and group 2 genotypes BEB4 (16/23 specimens), I (1/23 specimens), and J (1/23 specimens) from 7.0% (23/327 specimens) of yaks (18).…”
mentioning
confidence: 99%